2004
DOI: 10.1111/j.1399-6576.2004.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB involvement in the induction of high affinity CAT‐2 in lipopolysaccharide‐stimulated rat lungs

Abstract: NF-kappaB actively participates in the induction of CAT-2 and CAT-2B in intact animals. Our data further support the idea that CAT-2 and CAT-2B are crucial in regulating iNOS activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 63 publications
(84 reference statements)
2
18
0
Order By: Relevance
“…These data, in concert with our previous ones [21][22][23], indicated that expression of CAT-2 and CAT-2B is organ-specific. In consistent with previous data [13], we also confirmed that CAT-2A, i.e., the low affinity alternative transcript of CAT-2, was constitutively expressed in rat lungs, kidney, and liver.…”
Section: Figsupporting
confidence: 87%
“…These data, in concert with our previous ones [21][22][23], indicated that expression of CAT-2 and CAT-2B is organ-specific. In consistent with previous data [13], we also confirmed that CAT-2A, i.e., the low affinity alternative transcript of CAT-2, was constitutively expressed in rat lungs, kidney, and liver.…”
Section: Figsupporting
confidence: 87%
“…The doses (i.e., 2, 20, and 200 M) and timing for PDTC administration were chosen according to our previous report [17]. After 2 h of PDTC pretreatment, macrophages were treated with LPS or LPS plus clonidine and then harvested at 12 h after receiving LPS.…”
Section: Inhibition Of Nf-b Using the Nf-b Inhibitor Pyrrolidine Dithmentioning
confidence: 99%
“…As we previously reported [22], harvested tissues were homogenized and centrifuged at 40,000 ϫ g for 30 min. The pellet was then resuspended and sonicated with an ultrasonic dismembrator for 10 s at 40% power, and three cycles of freezing and thawing were performed, after which the sonication was repeated.…”
Section: Myeloperoxidase Activity Assaymentioning
confidence: 99%